Performance Comparison for Series and Parallel Modes of a Hybrid Electric Vehicle - Halit Yaşar; Gökhan Canbolat (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Recently, the studies in the automotive sector has concentratedon hybrid electric vehicle. The better results in fuel economy and vehicleperformance values have been achieved with the hybrid electric vehicletechnology. In this study, the fuel consumption and vehicle performance values arecompared to the series and parallel hybrid electric modes of a conventionalstreet sweeper by using AVL Cruise. Nowadays, there are many driving cyclesused in the analysis of fuel consumption and vehicle performans. However thecurrent driving cycles are not appropriate for the vehicles designed for aparticular function (carrying, lifting, sweeping etc.) such as street sweepersin terms of velocity and functionality. For this reason, a driving cycle wasconstructed by taking into consideration the daily tasks of the street sweeperswith the help of AVL Cruise. The series and parallel hybrid electricconfigurations of the street sweeper were analyzed separately. Consequently,the demanded power (kW) from the internal combustion engine and its fuelconsumption (L/h) were investiageted under the specific operating conditions inthe driving cycle. The simulations show that the series hybrid mode has betterfuel economy and vehicle performance.